Seasonal variation of Moniezia (Blanchard) in Capra hircus at Sangamner region, Ahmednagar district (M.S.), India - Bhagwan3, V.R. Pawade1*, V.M. Pulate2, H.K. (International Multidisciplinary Research Journal, 2011)
The present statistical communication deals with the study of seasonal variation of cestode Moniezia, along with incidence and intensity of the parasites according to the seasons in the year Oct 2007 to Sept 2008 at Sangmner region, district Ahmednagar. The seasonal variation of gastro-intestinal cestodes infection shows the high prevalence, which occur in winter (32.07%) following by Rainy (30 %) and summer (24.13%) because of easy dispersal of parasite resulting is increased in contact with the host and the parasites.